Electrode and secondary battery including the same

By integrating a carbon nanotube structure made of bonded single-walled carbon nanotube units and multi-walled carbon nanotube units into the electrode active material layer, the battery's conductivity and lifespan are improved, addressing the challenges of maintaining conductive networks in lithium secondary batteries.

JP2025061546AActive Publication Date: 2025-04-10LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025008524
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-10-04
Filing Date
2025-01-21
Publication Date
2025-04-10
Estimated Expiration
2040-09-29

AI Technical Summary

Technical Problem

Existing lithium secondary batteries face challenges in maintaining conductivity within the electrode active material layer due to damage or cutting of single-walled carbon nanotubes during charge and discharge cycles, leading to increased battery resistance and reduced lifespan.

Method used

Incorporating a carbon nanotube structure composed of two to 5,000 single-walled carbon nanotube units bonded together, along with multi-walled carbon nanotube units, into the electrode active material layer at a weight percentage of 0.01% to 0.5%, to form a stable and long-lasting conductive network.

Benefits of technology

The carbon nanotube structure maintains conductivity and forms a uniform, dense conductive network, reducing electrode resistance and enhancing the battery's input/output characteristics and high-temperature life characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061546000001_ABST
    Figure 2025061546000001_ABST
Patent Text Reader

Abstract

To provide: an electrode that has low resistance and can improve the input / output characteristics and high-temperature life characteristics of a battery; and a secondary battery including the electrode.SOLUTION: The present invention relates to an electrode and a secondary battery including the same, the electrode including an electrode active material layer, the electrode active material layer including an electrode active material and a conductive agent, the conductive agent including: a multi-walled carbon nanotube unit; and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure is contained in the electrode active material layer in an amount of 0.01 wt% to 0.5 wt%.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2019-0122963, filed on October 4, 2019, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to an electrode including an electrode active material layer, the electrode active material layer including an electrode active material and a conductive material, the conductive material including a multi-walled carbon nanotube unit and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, the carbon nanotube structure being included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %, and a secondary battery including the electrode. [Background technology]

[0003] Recently, as the technological development and demand for mobile devices increases, the demand for batteries as energy sources is rapidly increasing, and various researches are being conducted on batteries that can meet various demands. In particular, researches on lithium secondary batteries that have high energy density and excellent life and cycle characteristics as the power source for such devices are being actively conducted.

[0004] The lithium secondary battery refers to a battery including a positive electrode including a positive electrode active material capable of inserting / extracting lithium ions, a negative electrode including a negative electrode active material capable of inserting / extracting lithium ions, an electrode assembly in which a microporous separator is interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte containing lithium ions.

[0005] On the other hand, since the electrode active material alone cannot ensure the conductivity of the electrode, there is a problem that the resistance of the battery is excessively high, so that the electrode generally further contains a conductive material. Conventionally, a dot-like conductive material such as carbon black has been mainly used, and linear conductive materials such as carbon nanotubes and carbon nanofibers are also used to further improve the conductivity and the capacity of the battery.

[0006] Single-walled carbon nanotubes are one of the linear conductive materials, and improve the conductivity in the electrode active material layer due to their elongated shape. In the past, an electrode slurry was prepared using a dispersion liquid in which the single-walled carbon nanotubes are completely dispersed and exist as single-walled carbon nanotube units, and then an electrode active material layer was prepared using the electrode slurry. In the electrode active material layer, the single-walled carbon nanotube units exist separately. However, when the battery is repeatedly charged and discharged, the surface of the single-walled carbon nanotube is damaged or the single-walled carbon nanotube is broken, making it difficult to maintain the conductive network in the electrode active material layer. As a result, the conductive network is interrupted or reduced, which reduces the life characteristics of the battery.

[0007] For this reason, there is a method of using multi-walled carbon nanotubes to ensure conductivity despite surface damage of carbon nanotubes. However, in the case of multi-walled carbon nanotubes, due to the structure formed by growing in units of nodes, they are cut to an excessively short length during the preparation of the dispersion, so there is a limit to improving the conductivity of the electrode. Therefore, a method is required to introduce a new type of conductive material to reduce the resistance of the electrodes and improve the input / output characteristics and high-temperature life characteristics of the battery. Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present invention is to provide an electrode that has low resistance and can improve the input / output characteristics and high-temperature life characteristics of a battery. Another problem to be solved by the present invention is to provide a secondary battery including the electrode. [Means for solving the problem]

[0009] According to one embodiment of the present invention, there is provided an electrode comprising an electrode active material layer, the electrode active material layer comprising an electrode active material and a conductive material, the conductive material comprising a multi-walled carbon nanotube unit and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure is included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %. According to another embodiment of the present invention, there is provided a secondary battery including the electrode. Effect of the Invention

[0010] The electrode according to the present invention includes a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded together as a conductive material together with a multi-walled carbon nanotube unit, and therefore the conductive network can be smoothly maintained even during the charging and discharging process of the battery. Specifically, since the carbon nanotube structure has a form in which a plurality of single-walled carbon nanotube units are bonded in a line, the form can be maintained even when the battery is repeatedly charged and discharged, and therefore the conductive network can be smoothly maintained. In addition, since the carbon nanotube structure has a long length, it contributes to the formation of a long conductive network, and the multi-walled carbon nanotube units are mainly disposed on the surface of the electrode active material and contribute to the formation of a short conductive network, so that an overall uniform and dense conductive network can be derived. As a result, the resistance of the electrode can be maintained at a low level, and the input / output characteristics and high-temperature life characteristics of the battery can be improved. [Brief description of the drawings]

[0011] [Figure 1] 1 is a SEM photograph of a multi-walled carbon nanotube A and carbon nanotube structures B and C used in an embodiment of the present invention. [Diagram 2] 3 shows TEM and SEM images of a carbon nanotube structure A used in an embodiment of the present invention and a single-walled carbon nanotube unit B used in a comparative example. [Diagram 3] 1 is a SEM photograph of an electrode according to Example 1 of the present invention. [Figure 4] 1 is a SEM photograph of an electrode in Comparative Example 2 of the present invention. [Diagram 5] 1 is a SEM photograph of an electrode in Comparative Example 4 of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0013] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. The singular expressions include the plural expressions unless otherwise clearly indicated in the context.

[0014] As used herein, terms such as "comprise," "comprise," or "have" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, but should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.

[0015] In this specification, "%" means % by weight unless clearly indicated otherwise. In this specification, the "specific surface area" is measured by the BET method, and specifically, it can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan.

[0016] In this specification, the average particle size (D 50The average particle size (D) can be defined as the particle size corresponding to 50% of the cumulative volume in the particle size distribution curve. 50 ) can be measured, for example, by using a laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to several mm, and can provide results with high reproducibility and high resolution.

[0017] In the present invention, a single-walled carbon nanotube unit refers to a tubular unit having one wall made of carbon atoms, and a multi-walled carbon nanotube unit refers to a tubular unit having multiple walls made of carbon atoms in one tube.

[0018] The present invention will be specifically described below. electrode The electrode according to the present invention includes an electrode active material layer, the electrode active material layer including an electrode active material and a conductive material, the conductive material including a multi-walled carbon nanotube unit and a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other, and the carbon nanotube structure may be included in the electrode active material layer in an amount of 0.01 wt % to 0.5 wt %.

[0019] The electrode may include an electrode active material layer. The electrode may further include a current collector, in which case the electrode active material layer may be disposed on one or both sides of the current collector.

[0020] The current collector is not particularly limited as long as it is a material that does not induce chemical changes in the battery and has conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, alloys thereof, those having their surfaces treated with carbon, nickel, titanium, silver, or the like, or calcined carbon may be used.

[0021] The current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to strengthen the bonding force of the electrode active material. Further, the electrode current collector may be used in various forms such as a film, a sheet, a foil, a net, a porous body, a foam, a non-woven fabric body, etc.

[0022] The electrode active material layer may include an electrode active material and a conductive material. The electrode active material may be a positive electrode active material or a negative electrode active material generally used in the art, and its type is not particularly limited.

[0023] For example, as the positive electrode active material, a lithium oxide containing one or more metals such as cobalt, manganese, nickel, or aluminum and lithium may be used. More specifically, the lithium oxide is a lithium-manganese-based oxide (for example, LiMnO2, LiMn2O, etc.), a lithium-cobalt-based oxide (for example, LiCoO2, etc.), a lithium-nickel-based oxide (for example, LiNiO2, etc.), a lithium-nickel-manganese-based oxide (for example, LiNi 1-Y1 Mn Y1 O2 (where 0 < Y1 < 1), LiNi Z1 Mn 2-Z1 O4 (where 0 < Z1 < 2), etc.), a lithium-nickel-cobalt-based oxide (for example, LiNi 1-Y2 Co Y2 O2 (where 0 < Y2 < 1), etc.), a lithium-manganese-cobalt-based oxide (for example, LiCo 1-Y3 Mn Y3 O2 (where 0 < Y3 < 1), LiMn 2-Z2 Co Z2 O4 (where 0 < Z2 < 2), etc.), a lithium-nickel-cobalt-manganese-based oxide (for example, Li(Ni P1 Co Q1 Mn R1 )O2 (where 0 < P1 < 1, 0 < Q1 < 1, 0 < R1 < 1, P1 + Q1 + R1 = 1) or Li(Ni P2 Co Q2 Mn R2)O4 (where 0 < P2 < 2, 0 < R2 < 2, P2 + Q2 + R2 = 2), etc.), or lithium-nickel-cobalt-manganese-other metal (M) oxides (e.g., Li(Ni P3 Co Q3 Mn R3 M 1 S )O2 (where M 1 is selected from the group consisting of Al, Cu, Fe, V, Cr, Ti, Zr, Zn, Ta, Nb, Mg, B, W, and Mo, and P3, Q3, R3, and S are the atomic fractions of independent elements, where 0 < P3 < 1, 0 < Q3 < 1, 0 < R3 < 1, 0 < S < 1, and P3 + Q3 + R3 + S = 1).), etc.), and any one or two or more of these compounds may be included.

[0024] On the other hand, as the negative electrode active material, for example, carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; SiO v (0 < v < 2), metal oxides capable of doping and dedoping lithium such as SnO2, vanadium oxides, and lithium vanadium oxides; or composites containing the metallic compound and the carbonaceous material such as Si-C composites or Sn-C composites, etc. may be mentioned, and any one or two or more of these mixtures may be used. Also, a thin film of metallic lithium may be used as the negative electrode active material. Also, as the carbonaceous material, either low-crystalline carbon or high-crystalline carbon may be used.

[0025] The electrode active material may be contained in an amount of 70% by weight to 99.5% by weight, preferably 80% by weight to 99% by weight, based on the total weight of the electrode active material layer. When the content of the electrode active material satisfies the above range, excellent energy density, electrode adhesion, and electrical conductivity can be achieved. The conductive material may include multi-layer carbon nanotube units and carbon nanotube structures.

[0026] (1) Multi-walled carbon nanotube unit The multi-walled carbon nanotube units are mainly arranged on the surface of the electrode active material and contribute to forming a conductive network between adjacent electrode active materials. The multi-walled carbon nanotube units are not in a bundle but mostly exist individually and are mainly arranged on the surface of the electrode active material.

[0027] The average diameter of the multi-walled carbon nanotube units may be 5 nm to 200 nm, specifically 5 nm to 100 nm, and more specifically 5 nm to 50 nm. When the range is satisfied, the multi-walled carbon nanotube units are easily dispersed in a slurry for manufacturing an electrode, and the conductivity of the electrode can be improved. The average diameter corresponds to an average value of the top 100 multi-walled carbon nanotube units and the bottom 100 multi-walled carbon nanotube units having the largest inner diameter of the electrode observed by SEM or TEM.

[0028] The BET specific surface area of ​​the multi-walled carbon nanotube unit is 50m 2 / g~500m 2 / g, specifically 100m 2 / g~400m 2 / g, more specifically 150m 2 / g~300m 2 When the specific surface area is within the above range, the multi-walled carbon nanotube units can be appropriately dispersed, the manufacturing process can be maintained, and the conductive network can be maximized even with a small conductive material content. The BET specific surface area can be measured by a nitrogen adsorption BET method.

[0029] The average length of the multi-walled carbon nanotube units may be 0.1 μm to 100 μm, specifically 0.1 μm to 50 μm, more specifically 0.1 μm to 3 μm. When the range is satisfied, the multi-walled carbon nanotube units can be appropriately dispersed, and an electrode slurry with a high solid content can be used during electrode production, thereby maintaining the manufacturing processability. In addition, even with a small conductive material content, the formation of a conductive network can be maximized. The average length corresponds to an average value of the top 100 multi-walled carbon nanotube units and the bottom 100 multi-walled carbon nanotube units in terms of length within the electrode observed by SEM or TEM.

[0030] The multi-walled carbon nanotube units may be included in the electrode active material layer at 0.1 wt % to 1.0 wt %, specifically 0.2 wt % to 0.9 wt %, more specifically 0.3 wt % to 0.8 wt %. When the range is satisfied, the dispersion and stability of the multi-walled carbon nanotube units are enhanced, and a conductive network in the electrode is smoothly formed, thereby improving the input / output characteristics and high-temperature life characteristics of the battery.

[0031] (2) Carbon nanotube structure The carbon nanotube structure may include a plurality of single-walled carbon nanotube units. Specifically, the carbon nanotube structure may be a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are aligned and bonded to each other. More specifically, in consideration of the durability and conductive network of the electrode, the carbon nanotube structure is most preferably a carbon nanotube structure in which 2 to 4,500, preferably 50 to 4,000, more preferably 1,000 to 4,000 single-walled carbon nanotube units are bonded to each other.

[0032] In the carbon nanotube structure, the single-walled carbon nanotube units may be arranged and bonded side by side (long axes of the units are bonded parallel to each other to form a flexible cylindrical structure) to form the carbon nanotube structure. In the electrode, the carbon nanotube structures may be connected to each other to form a network structure.

[0033] A conventional electrode including carbon nanotubes is generally prepared by dispersing bundle-type or entangled-type carbon nanotubes (single-walled carbon nanotube units or multi-walled carbon nanotube units attached to or entangled with each other) in a dispersion medium to prepare a conductive material dispersion, and then using the conductive material dispersion. In this case, the carbon nanotubes are completely dispersed in the conventional conductive material dispersion, and exist as a conductive material dispersion in which single-stranded carbon nanotube units are dispersed. In the conventional conductive material dispersion, the carbon nanotube units are easily cut due to an excessive dispersion process, and have a shorter length than the initial length. In addition, the carbon nanotube units can be easily cut during the rolling process of the electrode, and there is a further problem that the carbon nanotube units (especially single-walled carbon nanotube units) are cut or the surface is damaged due to an excessive volume change of the electrode active material during the operation of the battery. As a result, there is a problem that the conductivity of the electrode is reduced, and the input / output characteristics and high-temperature life characteristics of the battery are reduced. Moreover, multi-walled carbon nanotube units have many structural defects due to the mechanism of nodal growth (not smooth linear shape, but nodes due to defects that occur during the growth process). Therefore, the multi-walled carbon nanotube units are more easily cut during the dispersion process (see A in FIG. 1), and the short cut multi-walled carbon nanotube units are more likely to aggregate with each other due to π-π stacking caused by the carbon surface bond structure (sp2) of the units. As a result, it is difficult to disperse them more uniformly in the electrode slurry.

[0034] In contrast, the carbon nanotube structure included in the electrode of the present invention has a rope-like shape in which 2 to 5,000 single-walled carbon nanotube units that are relatively free of structural defects and maintain high crystallinity are arranged side by side and connected to each other (see B and C of FIG. 1 and A of FIG. 2), and can smoothly maintain its length without being cut even when the volume of the electrode active material changes, so that the conductivity of the electrode can be maintained even during continuous charging and discharging of the battery. In addition, the high electrical conductivity of the single-walled carbon nanotube units with high crystallinity can increase the conductivity of the electrode, thereby significantly improving the input / output characteristics and high-temperature life characteristics of the battery. In addition, the carbon nanotube structures can be connected to each other in the electrode to form a network structure, so that excessive volume change of the electrode active material can be suppressed to prevent cracks from occurring and a strong conductive network can be secured. In addition, even if cracks occur in the electrode active material, the carbon nanotube structure can connect the electrode active material across the cracks, so that the conductive network can be maintained. In addition, since the carbon nanotube structure is not easily broken and can maintain a long shape, the conductive network can be strengthened throughout the electrode active material layer, and the electrode adhesive strength can be significantly improved by suppressing detachment of the electrode active material.

[0035] In particular, in terms of use in combination with the multi-walled carbon nanotube units, while the multi-walled carbon nanotube units are mainly disposed on the surface of the electrode active material to contribute to ensuring electrical conductivity in the short length, the carbon nanotube structure can contribute to ensuring electrical conductivity in the long length through its long length and network structure, thereby forming a uniform conductive network throughout the electrode active material layer.

[0036] In the carbon nanotube structure, the average diameter of the single-walled carbon nanotube units may be 0.5 nm to 5 nm, specifically, 1 nm to 5 nm. When the average diameter is satisfied, even a very small amount of conductive material is contained, it is possible to maximize the conductivity in the electrode. The average diameter corresponds to the average value of the top 100 single-walled carbon nanotube units and the bottom 100 single-walled carbon nanotube units having the largest diameter when the manufactured electrode is observed by TEM.

[0037] In the carbon nanotube structure, the average length of the single-walled carbon nanotube units may be 1 μm to 100 μm, specifically 5 μm to 50 μm. When the average length is satisfied, a long conductive path for conductive connection between the electrode active materials can be formed, and a unique network structure can be formed, so that even with a very small amount of conductive material, the conductivity within the electrode can be maximized. The average length corresponds to an average value of the top 100 single-walled carbon nanotube units and the bottom 100 single-walled carbon nanotube units in terms of length when the manufactured electrode is observed by TEM.

[0038] The specific surface area of ​​the single-walled carbon nanotube unit is 500m 2 / g~1,000m 2 / g, specifically 600m 2 / g~800m 2 / g. When the above range is satisfied, the wide specific surface area can smoothly secure a conductive path in the electrode, so that the conductivity in the electrode can be maximized even with a very small amount of conductive material. The specific surface area of ​​the single-walled carbon nanotube unit can be calculated from the nitrogen gas adsorption amount at liquid nitrogen temperature (77K) using BELSORP-mini II manufactured by BEL Japan.

[0039] The average diameter of the carbon nanotube structures may be 2 nm to 200 nm, specifically 5 nm to 150 nm, and more specifically 50 nm to 120 nm. When the above range is satisfied, it is effective for forming a conductive network structure, is advantageous for connecting active materials, and can realize excellent electrical conductivity. The average diameter corresponds to the average value of the diameters of the top 100 carbon nanotube structures and the bottom 100 carbon nanotube structures when the manufactured electrode is observed by SEM.

[0040] The average length of the carbon nanotube structures may be 1 μm to 500 μm, specifically 5 μm to 100 μm, and more specifically 10 μm to 70 μm. When the range is satisfied, it is effective for forming a conductive network, is advantageous for connecting between electrode active materials, and can realize excellent electrical conductivity. The average length corresponds to the average value of the lengths of the top 100 carbon nanotube structures and the bottom 100 carbon nanotube structures when the manufactured electrode is observed by SEM.

[0041] The carbon nanotube structure may be included in the electrode active material layer at 0.01 wt % to 0.5 wt %, specifically at 0.01 wt % to 0.15 wt %, and more specifically at 0.01 wt % to 0.1 wt %. When the above range is satisfied, the conductive path of the electrode is secured, and the electrode resistance is maintained at a low level while the life characteristics of the battery can be improved. When the bundle-type carbon nanotubes are completely dispersed (dispersed so that the carbon nanotube units are separated from each other at most by a general dispersion method) during the preparation of the conductive material dispersion, the carbon nanotube structure is not generated or, even if it is generated unintentionally, it is generated in a very small amount (for example, 0.0005 wt %). That is, the above content range cannot be achieved by a general method. The carbon nanotube structure has a form in which 2 to 5,000 single-walled carbon nanotube units are arranged and bonded to each other, so that the carbon nanotube structure can smoothly maintain its length without being cut even when the volume of the electrode active material changes. Therefore, the conductivity of the electrode can be maintained, and the high conductivity of the single-walled carbon nanotube unit can smoothly ensure the conductivity of the electrode, so that even if the content of the carbon nanotube structure in the electrode is low, the input / output characteristics and high-temperature life characteristics of the battery can be excellent. Meanwhile, in some cases, the single-walled carbon nanotube unit may be surface-treated by oxidation or nitridation to improve affinity with the dispersant.

[0042] The weight ratio of the multi-walled carbon nanotube unit to the carbon nanotube structure may be 100:1 to 100:200, specifically 100:2 to 100:100, and more specifically 100:5 to 100:50. When the weight ratio satisfies the above range, the solid content of the electrode slurry can be increased while the content of the conductive material for an appropriate level of conductivity can be reduced. In addition, the electrical conductivity and adhesive strength of the electrode can be improved at the same time, so that the input / output characteristics and high-temperature life characteristics of the battery can be significantly improved.

[0043] The electrode active material layer may further include a binder. The binder is for ensuring adhesion between the electrode active materials or between the electrode active material and the current collector, and may be a general binder used in the art, and the type is not particularly limited. Examples of the binder include vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination.

[0044] The binder may be included in an amount of 10 wt % or less, preferably 0.1 wt % to 5 wt %, based on the total weight of the electrode active material layer. When the binder content is within this range, an increase in electrode resistance can be minimized while excellent electrode adhesion can be achieved.

[0045] The electrode active material layer may further include at least one of polyvinylidene fluoride and hydrogenated nitrile butadiene rubber. The polyvinylidene fluoride and hydrogenated nitrile butadiene rubber assist in dispersing bundled or entangled single-walled carbon nanotubes or bundled or entangled multi-walled carbon nanotubes in a conductive material dispersion liquid used in the preparation of an electrode, and may be included in the electrode by preparing an electrode slurry from the conductive material dispersion liquid.

[0046] Electrode manufacturing method Next, a method for producing the electrode of the present invention will be described. The electrode manufacturing method of the present invention may include a step (S1) of preparing a multi-walled carbon nanotube unit dispersion liquid and a carbon nanotube structure dispersion liquid, and a step (S2) of forming an electrode slurry containing the multi-walled carbon nanotube unit dispersion liquid, the carbon nanotube structure dispersion liquid, and an electrode active material.

[0047] (1) Step (S1) of preparing a multi-walled carbon nanotube unit dispersion liquid and a carbon nanotube structure dispersion liquid 1) Preparation of multi-walled carbon nanotube unit dispersion The multi-walled carbon nanotube unit dispersion liquid can be prepared by preparing a mixture containing bundled or entangled multi-walled carbon nanotubes (combination or aggregate of multi-walled carbon nanotube units), a dispersion medium, and a dispersant, and then dispersing the bundled or entangled multi-walled carbon nanotubes completely (dispersing the multi-walled carbon nanotube units one by one) using a method such as a homogenizer, a bead mill, a ball mill, a basket mill, an attrition mill, a universal mixer, a clear mixer, a spike mill, a TK mixer, ultrasonic dispersion, etc. The dispersion medium and dispersant are the same as those used in the preparation of the carbon nanotube structure dispersion liquid described below, and will be described below.

[0048] 2) Preparation of carbon nanotube structure dispersion The preparation of the carbon nanotube structure dispersion liquid may include a step (S1-1) of preparing a mixture containing a dispersion medium, a dispersant, and bundled single-walled carbon nanotubes (a combination to aggregate of single-walled carbon nanotube units), and a step (S1-2) of applying a shear force to the mixture liquid to disperse the bundled single-walled carbon nanotubes and form a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are combined in a line.

[0049] In the step S1-1, the mixture can be prepared by adding the bundled single-walled carbon nanotubes and a dispersant to a dispersion medium. The bundled single-walled carbon nanotubes are the above-mentioned single-walled carbon nanotube units that are combined to form a bundle, and typically contain 2 or more, substantially 500 or more, for example 5,000 or more single-walled carbon nanotube units.

[0050] The specific surface area of ​​the bundled single-walled carbon nanotubes is 500m 2 / g~1,000m 2 / g, specifically 600m 2 / g~800m 2 When the above range is satisfied, the large specific surface area can smoothly secure a conductive path in the electrode, so that even if the conductive material content is very small, the conductivity in the electrode can be maximized.

[0051] The bundled single-walled carbon nanotubes may be contained in the mixture at 0.1 wt % to 1.0 wt %, specifically, at 0.2 wt % to 0.5 wt %. When the above range is satisfied, the bundled single-walled carbon nanotubes are dispersed at an appropriate level, a carbon nanotube structure at an appropriate level is formed, and dispersion stability is improved.

[0052] Examples of the dispersion medium include amide polar organic solvents such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, and octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, and hexylene glycol; polyhydric alcohols such as glycerin, trimethylolpropane, pentaerythritol, and sorbitol. Examples of the dispersing medium include, but are not limited to, alcohols; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, or tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl propyl ketone, or cyclopentanone; esters such as ethyl acetate, γ-butyl lactone, and ε-propiolactone, and any one or a mixture of two or more of these may be used. More specifically, the dispersing medium may be N-methylpyrrolidone (NMP).

[0053] The dispersant may include at least one of hydrogenated nitrile butadiene rubber, polyvinylidene fluoride, and carboxymethyl cellulose, and may be specifically polyvinylidene fluoride or hydrogenated nitrile butadiene rubber.

[0054] The weight ratio of the bundled carbon nanotubes to the dispersant in the conductive material dispersion may be 1:0.1 to 1:7, specifically 1:1 to 1:6. When the range is satisfied, the bundled single-walled carbon nanotubes are dispersed at an appropriate level, a carbon nanotube structure at an appropriate level can be formed, and dispersion stability can be improved.

[0055] The solid content in the mixture may be 0.1 wt% to 20 wt%, specifically 1 wt% to 10 wt%. When the above range is satisfied, the bundled single-walled carbon nanotubes are dispersed at an appropriate level, a carbon nanotube structure at an appropriate level may be formed, and dispersion stability may be improved. In addition, the electrode slurry may have a viscosity and elasticity suitable for the electrode manufacturing process, which contributes to increasing the solid content of the electrode slurry.

[0056] In the step S1-2, the process of dispersing the bundled carbon nanotubes in the mixture may be performed using a mixing device such as a homogenizer, a bead mill, a ball mill, a basket mill, an attrition mill, a universal mixer, a clear mixer, a spike mill, a TK mixer, or an ultrasonic dispersion (sonification) device, etc. Among them, the bead mill method is preferred because it is possible to precisely control the diameter size of the carbon nanotube structure, to achieve uniform distribution of the carbon nanotube structure, and is advantageous in terms of cost.

[0057] The bead mill method is as follows: the mixture is placed in a container containing beads, and the container is rotated to disperse the bundled single-walled carbon nanotubes. At this time, the conditions for carrying out the bead mill method are as follows.

[0058] The average particle size of the beads may be 0.5 mm to 1.5 mm, specifically 0.5 mm to 1.0 mm. When the above range is satisfied, the carbon nanotube structure is not broken during the dispersion process, the diameter can be appropriately controlled, and a dispersion solution with a uniform composition can be produced.

[0059] The rotation speed of the container may be 500 RPM to 10,000 RPM, specifically 2,000 RPM to 6,000 RPM. When the above range is satisfied, the carbon nanotube structure is not broken during the dispersion process, the diameter can be appropriately controlled, and a dispersion solution with a uniform composition can be produced.

[0060] The time for which the bead mill is used may be 0.5 to 2 hours, specifically 0.5 to 1.5 hours, and more specifically 0.8 to 1 hour. When the above range is satisfied, the carbon nanotube structure is not broken during the dispersion process, and the diameter can be appropriately controlled, so that a dispersion solution with a uniform composition can be produced. The time for which the bead mill is used means the total time for which the bead mill is applied, and therefore, for example, if the bead mill is used several times, it means the total time over the several times.

[0061] The bead mill conditions are for dispersing the bundled single-walled carbon nanotubes to an appropriate level, specifically, excluding the case where the bundled single-walled carbon nanotubes are completely dispersed into a single single-walled carbon nanotube. That is, the bead mill conditions are for dispersing the bundled single-walled carbon nanotubes to an appropriate level and forming a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are aligned and bonded to each other in the conductive material dispersion liquid produced. This can only be achieved when the composition of the mixture liquid, dispersion (e.g., bead mill) process conditions, etc. are strictly controlled. Through the above process, a carbon nanotube structure dispersion liquid can be formed.

[0062] (2) forming an electrode slurry containing the multi-walled carbon nanotube unit dispersion, the carbon nanotube structure dispersion, and an electrode active material (S2); When the multi-walled carbon nanotube unit dispersion and the carbon nanotube structure dispersion are prepared through the above-mentioned process, an electrode slurry is formed by mixing the dispersion and an electrode active material. In this case, the electrode active material may be the above-mentioned electrode active material.

[0063] In this case, the electrode active material can be mixed with the carbon nanotube structure dispersion liquid first, and then the multi-walled carbon nanotube unit dispersion liquid can be added. If the mixing order is reversed, the carbon nanotube structure cannot be dispersed due to π-π bonds, and the electrode active materials cannot be connected to each other, and the carbon nanotube structure exists in agglomeration, so that the conductive network of the electrode is not effectively formed.

[0064] The electrode slurry may further contain a binder and a solvent, if necessary. In this case, the binder may be the binder of the above-mentioned embodiment. Examples of the solvent include amide polar organic solvents such as dimethylformamide (DMF), diethylformamide, dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP); alcohols such as methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol), 1-butanol (n-butanol), 2-methyl-1-propanol (isobutanol), 2-butanol (sec-butanol), 1-methyl-2-propanol (tert-butanol), pentanol, hexanol, heptanol, and octanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, and hexylene glycol; polyhydric alcohols such as glycerin, trimethylolpropane, pentaerythritol, and sorbitol. Examples of the solvent include, but are not limited to, alcohols; glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol monoethyl ether, tetraethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, triethylene glycol monobutyl ether, and tetraethylene glycol monobutyl ether; ketones such as acetone, methyl ethyl ketone, methyl propyl ketone, and cyclopentanone; esters such as ethyl acetate, γ-butyl lactone, and ε-propiolactone, and any one or a mixture of two or more of these may be used. The solvent may be the same as or different from the dispersion medium used in the previous dispersion, and may preferably be N-methylpyrrolidone (NMP, N-methylpyrrolidone).

[0065] Next, the electrode slurry prepared as above is dried to form an electrode active material layer. Specifically, the electrode active material layer can be formed by a method of applying the electrode slurry on an electrode current collector and then drying it, or by applying the electrode slurry on another support and then peeling it off from the support to obtain a film, which is then laminated on a current collector. If necessary, after forming the electrode active material layer through the above method, a rolling process can be further performed. In this case, the drying and rolling can be performed under appropriate conditions in consideration of the physical properties of the electrode to be finally manufactured, and are not particularly limited.

[0066] secondary battery A secondary battery according to another embodiment of the present invention may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode may be the electrode according to the other embodiment described above. More specifically, the electrode according to the other embodiment described above may be the positive electrode according to this embodiment.

[0067] The separator is a separator that separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a normal porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be selectively used as a single layer or multilayer structure.

[0068] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0069] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt. Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0070] In particular, among the carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate are preferably used since they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts, and when such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants such as dimethyl carbonate and diethyl carbonate in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore such a mixture is more preferably used.

[0071] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte solution. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2- , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - One or more selected from the group consisting of may be used.

[0072] In addition to the components of the electrolyte, the electrolyte may further include one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0073] According to another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate characteristics, and high cycle characteristics, and therefore can be used as a power source for medium to large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0074] The present invention will be described in more detail below through specific examples and comparative examples. Preparation Example 1: Preparation of multi-walled carbon nanotube unit dispersion A mixture was prepared by mixing bundled multi-walled carbon nanotubes, hydrogenated nitrile butadiene rubber (H-NBR) as a dispersant, and N-methylpyrrolidone (NMP) as a dispersion medium in a weight ratio of 4:0.8:95.2. The mixture was dispersed in a spike mill filled with 80% beads of 0.65 mm in size, and discharged at a discharge speed of 2 kg / min. This process was repeated twice to completely disperse the bundled multi-walled carbon nanotubes, producing a multi-walled carbon nanotube unit dispersion.

[0075] Production Example 2: Production of carbon nanotube structure dispersion A bundle of single-walled carbon nanotubes (specific surface area: 650 m2) consisting of single-walled carbon nanotube units with an average diameter of 1.5 nm and an average length of 5 μm or more. 2 A mixture was prepared by mixing polyvinylidene fluoride (PVdF, KF9700, weight average molecular weight: 880,000 g / mol) and polyvinylidene fluoride (PVdF, KF9700, weight average molecular weight: 880,000 g / mol) in a solvent N-methylpyrrolidone (NMP) to prepare a mixture with a solid content of 2.4 wt%.

[0076] The mixture was stirred using a bead mill to disperse the bundled single-walled carbon nanotubes in the solvent, producing a carbon nanotube structure dispersion. The beads had a particle size of 1 mm, the stirring vessel containing the beads was rotated at 3,000 RPM, and the stirring was performed for 60 minutes. The carbon nanotube structure dispersion contained carbon nanotube structures in which 2 to 5,000 single-walled carbon nanotube units were aligned and bound together (see FIG. 2A).

[0077] In the carbon nanotube structure dispersion liquid, the carbon nanotube structure was present at 0.4% by weight, and the polyvinylidene fluoride was present at 2.0% by weight.

[0078] Production Example 3: Production of Carbon Black Dispersion Specific surface area is 240m 2 / g of carbon black (in the form of secondary particles consisting of primary particles with an average diameter of 25 nm) and hydrogenated nitrile butadiene rubber (weight average molecular weight: 260,000 g / mol) were mixed in a solvent N-Methylpyrrolidone (NMP) to prepare a mixture with a solid content of 16.5 wt%.

[0079] The mixture was stirred using a beads mill to disperse the carbon black in the solvent to prepare a carbon black dispersion, where the beads had a particle size of 1 mm, the rotation speed of the stirring vessel containing the beads was 3,000 RPM, and the stirring was performed for 60 minutes.

[0080] In the carbon black dispersion, the carbon black was 15% by weight and the hydrogenated butadiene rubber was 1.5% by weight.

[0081] Preparation Example 4: Preparation of Single-Walled Carbon Nanotube Unit Dispersion A bundle of single-walled carbon nanotubes (specific surface area: 650 m2) consisting of single-walled carbon nanotube units with an average diameter of 1.5 nm and an average length of 5 μm or more. 2The bundled carbon nanotubes (0.4 wt %; hydrogenated nitrile butadiene rubber 4.0 wt %) and hydrogenated nitrile butadiene rubber (weight average molecular weight: 260,000 g / mol) were mixed in a solvent N-methylpyrrolidone (NMP) to produce a mixture with a solid content of 4.4 wt % (bundle-type carbon nanotubes 0.4 wt %, hydrogenated nitrile butadiene rubber 4.0 wt %).

[0082] The mixture was stirred in a bead mill to disperse the bundled single-walled carbon nanotubes in the solvent, producing a conductive material dispersion. At this time, the particle size of the beads was 1 mm, and the rotation speed of the stirring vessel containing the beads was 3,000 RPM. Stirring was performed for a total of 4 cycles (with natural cooling for 60 minutes between each cycle) under the above conditions, with 60 minutes of stirring being one cycle. As a result, a single-walled carbon nanotube unit dispersion was produced (see B in FIG. 2). In the dispersion, the bundled single-walled carbon nanotubes were completely dispersed, and the single-walled carbon nanotube units were present as single units, and the above-mentioned carbon nanotube structure was not detected. In addition, the carbon nanotube structure was 0.4 wt % and the hydrogenated butadiene rubber was 4.0 wt % in the single-walled carbon nanotube unit dispersion.

[0083] Examples and Comparative Examples Example 1: Preparation of the positive electrode The multi-walled carbon nanotube unit dispersion of Production Example 1, the carbon nanotube structure dispersion of Production Example 2, and Li[Ni 0.6 Co 0.2 Mn 0.2 ]O2 (NCM622) and a binder (PVDF, KF9700) were mixed with N-methylpyrrolidone (NMP) to prepare a positive electrode slurry with a solid content of 70.4%. The positive electrode slurry was applied onto an Al thin film current collector with a thickness of 20 μm, and then dried at 130° C. and rolled to prepare a positive electrode including a positive electrode active material layer.

[0084] In the positive electrode active material layer, the LiNi 0.6 Co 0.2Mn 0.2 The O2 (NCM622) was 97.5 wt%, the binder was 1.67 wt%, the hydrogenated nitrile butadiene rubber was 0.13 wt%, the multi-walled carbon nanotube unit was 0.65 wt%, and the carbon nanotube structure was 0.05 wt%.

[0085] Referring to FIG. 3, it can be seen that in the positive electrode of Example 1, rope-like carbon nanotube structures are formed long and form a network structure, connecting the NCM622.

[0086] Example 2: Preparation of the positive electrode A positive electrode was manufactured in the same manner as in Example 1, except that the amount of the multi-walled carbon nanotube unit dispersion of Preparation Example 1 and the carbon nanotube structure dispersion of Preparation Example 2 were different, and the multi-walled carbon nanotube unit was contained in the final positive electrode at 0.6 wt % and the carbon nanotube structure was contained at 0.1 wt %.

[0087] Comparative Example 1: Production of Positive Electrode A positive electrode was manufactured in the same manner as in Example 1, except that the carbon black dispersion of Preparation Example 3 was used instead of the multi-walled carbon nanotube unit dispersion of Preparation Example 1 and the carbon nanotube structure dispersion of Preparation Example 2.

[0088] Comparative Example 2: Production of Positive Electrode A positive electrode was manufactured in the same manner as in Example 1, except that the carbon nanotube structure dispersion liquid of Preparation Example 2 was not used, and the multi-walled carbon nanotube unit dispersion liquid of Preparation Example 1 was used in the same amount (only the multi-walled carbon nanotube unit dispersion liquid of Preparation Example 1 was used).

[0089] Comparative Example 3: Production of Positive Electrode A positive electrode was manufactured in the same manner as in Example 1, except that the multi-walled carbon nanotube unit dispersion liquid of Preparation Example 1 was not used, and the carbon nanotube structure dispersion liquid of Preparation Example 2 was used in the same amount (only the carbon nanotube structure dispersion liquid of Preparation Example 2 was used).

[0090] Comparative Example 4: Production of Positive Electrode A positive electrode was manufactured in the same manner as in Example 1, except that the single-walled carbon nanotube unit dispersion liquid of Preparation Example 4 was used instead of the carbon nanotube structure dispersion liquid of Preparation Example 2.

[0091] [Table 1]

[0092] In the examples 1, 2, and comparative example 3, the carbon nanotube structures had an average diameter of 100 nm and an average length of 15.6 μm. In the examples and comparative examples, the multi-walled carbon nanotube units had an average diameter of 10.8 nm and an average length of 1.3 μm. In the comparative example 4, the single-walled carbon nanotube units had an average diameter of 1.6 nm and an average length of 1.8 μm.

[0093] The average diameter and average length correspond to the average values ​​of the top 100 carbon nanotube structures (or multi-walled carbon nanotube units, or single-walled carbon nanotube units) and the bottom 100 carbon nanotube structures (or multi-walled carbon nanotube units, single-walled carbon nanotube units) having the largest diameter (or length) when the manufactured positive electrode is observed by TEM.

[0094] Experimental example 1: Observation of the positive electrode The positive electrode active material layers of the positive electrodes of Example 1, Comparative Example 2 and Comparative Example 4 were observed by a scanning electron microscope. Referring to FIG. 3, it can be seen that in Example 1, the flexible, long rope-like carbon nanotube structure (in which 2 to 5,000 single-walled carbon nanotube units are arranged in parallel and bonded to each other) and the multi-walled carbon nanotube units form a well-conductive network within the positive electrode active material layer.

[0095] On the other hand, referring to Fig. 4, only the multi-walled carbon nanotube units are formed in a short length, and no long rope-like flexible carbon nanotube structure is observed as in Example 1. Also, referring to Fig. 5, only the multi-walled carbon nanotube units and the single-walled carbon nanotube units are observed, and no long rope-like carbon nanotube structure is observed.

[0096] Experimental example 2: Evaluation of battery input / output characteristics Using the positive electrodes of Examples 1 and 2 and Comparative Examples 1 to 4, batteries were produced as follows. The negative electrode slurry was prepared by mixing artificial graphite as the negative electrode active material, carbon black as the negative electrode conductive material, styrene-butadiene rubber (SBR) as the negative electrode binder, and carboxymethyl cellulose (CMC) in a weight ratio of 96.1:0.5:2.3:1.1 with distilled water. The slurry was applied to a negative electrode current collector (Cu) with a thickness of 20 μm at a loading amount of 10 mg / cm. 2 The negative electrode current collector on which the negative electrode slurry was disposed was rolled by a roll rolling method so that the total thickness of the negative electrode slurry and the negative electrode current collector was 80 μm. The negative electrode slurry and the negative electrode current collector were then dried at 110° C. for 6 hours to prepare a negative electrode. Then, the prepared negative electrode and the above-mentioned positive electrode were combined with a 15 μm-thick polyethylene separator interposed therebetween to prepare a monocell, and an electrolyte (ethylene carbonate (EC) / ethyl methyl carbonate (EMC)=1 / 2 (volume ratio), lithium hexafluorophosphate (LiPF61 mol)) was injected into the monocell to prepare a lithium secondary battery.

[0097] The input / output characteristics were evaluated as follows and are shown in Table 2. The lithium secondary battery was charged / discharged at 0.33C / 0.33C in the voltage range of 4.25V to 2.8V at 25°C, then charged again at 0.33C to 4.25V, and discharged at 0.33C while setting the SOC (State of Charge) at 35% (SOC 100% was set based on the discharge capacity of 2.8V).Then, the resistance value was calculated with respect to the voltage change when the battery was continuously discharged at 0.4C at -10°C for 1350 seconds.

[0098] Experimental Example 3: Evaluation of high-temperature battery life characteristics Using the positive electrodes of Examples 1 and 2 and Comparative Examples 1 to 4, secondary batteries as in Experimental Example 2 were manufactured. Each lithium secondary battery was charged / discharged at 0.33 C / 0.33 C in the voltage range of 4.25 V to 2.8 V at 45° C. for a total of 100 cycles. The discharge capacity after 100 cycles (capacity retention rate) was evaluated based on the discharge capacity after 1 cycle as 100%. The results are shown in Table 2.

[0099] [Table 2]

Claims

1. An electrode active material layer is included, The electrode active material layer includes an electrode active material and a conductive material, The conductive material is A multi-walled carbon nanotube unit; a carbon nanotube structure in which 2 to 5,000 single-walled carbon nanotube units are bonded to each other; The carbon nanotube structure is contained in the electrode active material layer in an amount of 0.01% by weight to 0.5% by weight.

2. 2. The electrode of claim 1, wherein a weight ratio of the multi-walled carbon nanotube unit to the carbon nanotube structure is 100:1 to 100:

200.

3. The electrode according to claim 1 or 2, wherein the multi-walled carbon nanotube unit is contained in the electrode active material layer in an amount of 0.1% by weight to 1.0% by weight.

4. The electrode according to claim 1 , wherein the carbon nanotube structures are interconnected to each other within the electrode to form a network structure.

5. In the carbon nanotube structure, The electrode according to claim 1 , wherein the single-walled carbon nanotube units are arranged side by side and bonded together.

6. 6. The electrode according to claim 1, wherein the carbon nanotube structure has an average length of 1 μm to 500 μm.

7. 7. The electrode according to claim 1, wherein the carbon nanotube structure has an average length of 10 μm to 70 μm.

8. 8. The electrode according to claim 1, wherein the carbon nanotube structure has an average diameter of 2 nm to 200 nm.

9. 9. The electrode according to claim 1, wherein the carbon nanotube structure has an average diameter of 50 nm to 120 nm.

10. 10. The electrode of claim 1, wherein in the carbon nanotube structure, the single-walled carbon nanotube units have an average diameter of 0.5 nm to 5 nm.

11. The electrode according to claim 1 , wherein the multi-walled carbon nanotube unit has an average diameter of 5 nm to 200 nm.

12. The electrode according to claim 1 , wherein the multi-walled carbon nanotube unit has an average length of 0.1 μm to 100 μm.

13. The electrode according to claim 1 , wherein the carbon nanotube structure is a carbon nanotube structure in which 50 to 4,000 single-walled carbon nanotube units are bonded to each other.

14. 14. The electrode of claim 1, wherein the electrode is a positive electrode.

15. A secondary battery comprising the electrode according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Electrode for power storage device, and its manufacturing method

    JP2008010681A

  • Conductive material dispersion and lithium secondary battery manufactured using the same

    JP2018534747A